Efeito agudo da pressão positiva expiratória versus técnica de Breath Stacking no pós-operatório de cirurgia cardíaca: ensaio randomizado cruzado - Nichele, Lidiane de Fátima Ilha (2019)
Patients submitted to cardiac surgery may develop postoperative pulmonary complications. Physical therapy uses techniques and equipment that reduce these complications. The Breath Stacking (BS) technique and Expiratory Positive Airway Pressure (EPAP) are used to achieve greater lung expansion and to improve clinical and functional outcomes in the postoperative period of cardiothoracic surgery. The aim of this study was to compare the acute effects of EPAP and BS on cardiopulmonary and physiological variables of postoperative eletive cardiac surgery patients during hospitalization and to analyze interventions safety aspects. This randomized crossover clinical trial was conducted at the Intensive Cardiology Unit, Medical Clinic I and Medical Clinic II of the University Hospital of Santa Maria, with a sample of 24 individuals undergoing cardiac surgery. Patients received EPAP with 10 cmH20 for 5 minutes and BS in 3 series of 5 applications, with sustained inspiration for 20 seconds, both using a siliconized face mask, in randomized order, with a 24-hour interval between each intervention. Preoperative screening and analysis of medical records were carried and spirometry, ventilometry, thoracoabdominal mobility, maximal respiratory pressures, vital signs and peripheral oxygen saturation were evaluated. In the postoperative period (before and after the interventions) all the above evaluations were performed again. Before, after and 10 min after the interventions, the following patient safety variables were recorded: degree of dyspnea, painful perception in the surgical incision, signs of respiratory distress, hemodynamic and respiratory responses. The evaluator was blinded as to the type of intervention. The study showed that EPAP increased FVC (P <0.003), FEV1 (P <0.024), and axillary (P = 0.030) and xiphoid (P = 0.002) amplitude coefficients. BS improved the abdominal amplitude coefficient (P <0.003). Both techniques increase RR similarly (EPAP: 3.0 bpm, 95% CI 0.98 to 5.01; BS: 2.2 bpm, 95% CI 0.19 to 4.21), which decreased after 10 min (EPAP: -1.8 bpm, 95% CI -3.30 to -0.33; BS: -2.3 bpm, 95% CI -3.83 to -0.83). EPAP reduced MAP (-4.1 mmHg, 95% CI -8.03 to -0.21), which remained lower after 10 min (-5.0 mmHg, 95% CI -8.95 to -1.13). In the other variables there were no changes in response to interventions. It concludes that a single application of EPAP improved FVC, FEV1 and axillary and xiphoid expansibility, which suggests broader effects compared to BS. The techniques proved to be safe in the respiratory and hemodynamic aspects, making these findings as auxiliaries in the physiotherapeutic decision making after cardiac surgery.